Composition and method for producing same
A resin composition with a controlled phase-separated structure addresses the compatibility issues of cross-copolymers with PP, enhancing tensile properties and impact resistance through ethylene-olefin-aromatic polyene copolymers and aromatic vinyl compounds, resulting in improved mechanical performance.
Patent Information
- Application Number
- JP2020128641
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-29
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2040-07-29
AI Technical Summary
The low compatibility and dispersibility of cross-copolymers with polypropylene (PP) limit their effectiveness as PP modifiers, particularly due to the lack of durability and heat resistance in polybutadiene and polyisoprene chains, which also increase the cost through hydrogenation processes.
A resin composition comprising polypropylene (A), olefin resin (B), and aromatic vinyl resin (C) with a specific phase-separated structure, where the dispersed phase c has an average diameter of 50 nm to 1 μm and a distance of 300 nm to 1500 nm, achieved through a method involving single-site coordination polymerization and graft copolymerization using ethylene-olefin-aromatic polyene copolymers and aromatic vinyl compounds.
The composition exhibits enhanced tensile properties, impact resistance, and dispersibility, making it suitable for thermoplastic elastomers with improved mechanical performance.
Smart Images

Figure 0007602879000006 
Figure 0007602879000007 
Figure 0007602879000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition and a method for making the same. [Background technology]
[0002] In the past, polymer blends and polymer alloys have been studied for improving the physical properties of resins by mixing resins with different properties to modify the properties of the resin. Polypropylene resin compositions are widely used in machine parts, automobile parts, etc., and in recent years, there has been a demand for polypropylene resin compositions that are excellent in productivity and excellent in impact resistance, rigidity, tensile and flexural modulus at room and low temperatures in pursuit of economic efficiency.
[0003] Hydrogenated block copolymers such as SEPS and SEBS are added to polypropylene resins to improve their impact resistance. Hydrogenated block copolymers are produced from styrene and dienes such as butadiene and isoprene by anionic living polymerization and subsequent hydrogenation. However, the market conditions of the dienes, the raw materials, often change significantly, and there are only a limited number of suppliers of isoprene. Furthermore, polybutadiene and polyisoprene chains contain double bonds, which means that they lack durability and heat resistance as they are, and therefore need to be hydrogenated, but the hydrogenation process increases the cost of hydrogenated block copolymers.
[0004] On the other hand, a technology has been disclosed in which a vinylbenzene-containing olefin copolymer is synthesized without a hydrogenation step by utilizing a single-site coordination polymerization catalyst with high polymerization activity for olefins, and then this copolymer is used to polymerize a vinyl compound such as styrene, thereby copolymerizing the divinylbenzene units in the copolymer to produce a cross-copolymer having both polyolefin chain and vinyl compound polymer chain block chains in the molecular structure (Patent Documents 1, 2, and 3). [Patent Document 1] WO2000 / 037517 publication [Patent Document 2] WO2007 / 139116 publication [Patent Document 3] US6414102 publication Summary of the Invention [Problem to be solved by the invention]
[0005] However, since the cross-copolymer is a cross-linked component, it has low compatibility with PP (polypropylene) and low dispersibility in PP, so improvements were required for its use as a PP modifier. [Means for solving the problem]
[0006] The present invention, which solves the above problems, comprises the following: One aspect of the present invention is Contains 50-90 wt% of polypropylene resin (A), 5-25 wt% of olefin resin (B), and 5-25 wt% of aromatic vinyl resin (C), A continuous phase a made of the polypropylene-based resin; a dispersed phase b containing the olefin-based resin dispersed in a continuous phase a; The dispersed phase c is made of the aromatic vinyl resin, Dispersed phase c is present in continuous phase a, or dispersed phase c is present in dispersed phase b, or dispersed phase c is present at the interface between continuous phase a and dispersed phase b, A composition in which, in a resin phase separation structure observed with a transmission electron microscope, the average equivalent circle diameter of the dispersed phase c is 50 nm or more and 1 μm or less, and the average distance between the centers of gravity of the dispersed phase c is 300 nm or more and 1500 nm or less. It is.
[0007] The aromatic vinyl resin may contain a graft copolymer. The polypropylene resin (A) and the olefin resin (B) may contain an α-olefin-propylene copolymer. The main chain of the graft copolymer may contain an ethylene-olefin-aromatic polyene copolymer. The number of carbon atoms of the olefin monomer may be 3 to 12. The main chain of the graft copolymer may have a composition in which the olefin (not including ethylene) content is 3 to 50 mol%, the aromatic polyene content is 0.1 to 1 mol%, and the remainder is ethylene content. The main chain of the graft copolymer may have a mass average molecular weight of 50,000 to 100,000. The side chain of the graft copolymer may contain an aromatic vinyl compound. The side chain of the graft copolymer may have a mass average molecular weight of 50,000 to 50,000. The composition may have a tensile modulus of 700 to 1100 MPa, a breaking elongation of 90 to 300%, and a breaking strength of 10 to 18 MPa, measured at a tensile speed of 50 mm / min in accordance with JIS K6251. The composition has a Charpy impact strength of 5 to 25 kJ / m at 23°C measured with a notch in accordance with JIS K7111-1. 2 may be also possible.
[0008] Another aspect of the present invention is a coordination polymerization step of synthesizing an ethylene-olefin-aromatic polyene copolymer from an ethylene monomer, an olefin monomer, and an aromatic polyene using a single-site coordination polymerization catalyst; a grafting step of synthesizing a graft copolymer containing the ethylene-olefin-aromatic polyene copolymer and an aromatic vinyl compound polymer by using an aromatic vinyl compound monomer and an anionic polymerization initiator or a radical polymerization initiator, The graft copolymer is synthesized in a solution in a coordination polymerization step. It is.
[0009] A method for producing a composition, comprising a kneading step of kneading an aromatic vinyl resin (C) containing the graft copolymer produced by the above production method, a polypropylene resin (A) and an olefin resin (B), wherein the composition is Contains 50-90 wt% of polypropylene resin (A), 5-25 wt% of olefin resin (B), and 5-25 wt% of aromatic vinyl resin (C), A continuous phase a made of the polypropylene-based resin; a dispersed phase b containing the olefin-based resin dispersed in a continuous phase a; The dispersed phase c is made of the aromatic vinyl resin, Dispersed phase c is present in continuous phase a, or dispersed phase c is present in dispersed phase b, or dispersed phase c is present at the interface between continuous phase a and dispersed phase b, A method for producing a composition, characterized in that in a resin phase separation structure observed by a transmission electron microscope, the average equivalent circle diameter of the dispersed phase c is 50 nm or more and 1 μm or less, and the average distance between the centers of gravity of the dispersed phase c is 300 nm or more and 1500 nm or less. The polypropylene resin (A) and the olefin resin (B) may each contain an α-olefin-propylene copolymer.
[0010] Another aspect of the present invention is a resin composition containing the above composition. Effect of the Invention
[0011] The present invention has excellent tensile properties, impact resistance, and dispersibility. [Brief description of the drawings]
[0012] [Figure 1] 1 shows a schematic diagram of a resin phase separation structure in a composition according to the present embodiment, observed by a transmission electron microscope. a shows a continuous phase made of polypropylene, b shows a dispersed phase containing an olefin-based resin, and c shows a dispersed phase made of an aromatic vinyl-based resin. Dispersed phase c includes dispersed phase c1 present in continuous phase a, dispersed phase c2 present in dispersed phase b, and dispersed phase c3 present at the interface between continuous phase a and dispersed phase b. [Diagram 2] 2A and 2B are transmission electron micrographs of the composition according to the present embodiment. a indicates a continuous phase made of polypropylene, b indicates a dispersed phase containing an olefin-based resin, and c indicates a dispersed phase made of an aromatic vinyl-based resin. c1 indicates dispersed phase c present in the continuous phase a, c2 indicates dispersed phase c present in the dispersed phase b, and c3 indicates dispersed phase c present at the interface between the continuous phase a and the dispersed phase b. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the embodiments of the present invention will be described in detail. In this specification, the symbol "~" means a range of values "greater than or equal to" and "less than or equal to" the values at both ends. For example, "A~B" means A or greater and B or less.
[0014] <Graft copolymer> The aromatic vinyl resin (C) of the present invention preferably contains a graft copolymer. The graft copolymer of the present invention is a copolymer obtained by a graft copolymer production method comprising: a coordination polymerization step of copolymerizing an ethylene monomer, an olefin monomer, and an aromatic polyene using a single-site coordination polymerization catalyst to synthesize an ethylene-olefin-aromatic polyene copolymer; and a grafting step of synthesizing a graft copolymer containing the ethylene-olefin-aromatic polyene copolymer and an aromatic vinyl compound polymer using an aromatic vinyl compound monomer and an anionic polymerization initiator or a radical polymerization initiator, wherein the graft copolymer is synthesized in a solution in the coordination polymerization step.
[0015] In the graft copolymer, the olefin monomer (a monomer unit derived from an olefin monomer in an ethylene-olefin-aromatic polyene copolymer, but not including ethylene) is preferably an olefin monomer having 3 to 12 carbon atoms, for example, an α-olefin, norbornene, vinylcyclohexane, or other cyclic olefin. The olefin monomer used may be one or more kinds. It is preferably an α-olefin having 4 to 12 carbon atoms, and is at least one kind selected from 1-butene, 1-hexene, and 1-octene. It is most preferably 1-hexene and / or 1-octene. It is also most preferable to use a plurality of olefin monomers in which 1-hexene and / or 1-octene account for the majority.
[0016] In the graft copolymer, the aromatic polyene is not particularly limited, and conventionally known aromatic polyenes can be used. The aromatic polyene is preferably an aromatic polyene having 10 to 30 carbon atoms, having a plurality of double bonds (e.g., vinyl groups are preferred) and one or more aromatic groups, capable of coordination polymerization, from the viewpoint of accelerating the polymerization reaction and various physical properties of the resulting polymer, more preferably an aromatic polyene in which one of the double bonds (e.g., vinyl groups are preferred) is used in coordination polymerization and the remaining double bond in the polymerized state is capable of anion polymerization or radical polymerization, and even more preferably divinylbenzene. As the divinylbenzene, one or more types selected from orthodivinylbenzene, paradivinylbenzene and metadivinylbenzene are preferred.
[0017] In the graft copolymer, examples of the aromatic vinyl compound monomer include styrene and various substituted styrenes, such as p-methylstyrene, m-methylstyrene, o-methylstyrene, ot-butylstyrene, mt-butylstyrene, pt-butylstyrene, p-chlorostyrene, o-chlorostyrene, etc. Among these, one or more selected from styrene, p-methylstyrene, and p-chlorostyrene are preferred, and styrene is more preferred.
[0018] The method for producing the graft copolymer used in the composition of the present invention will be described in detail below. The composition of the ethylene-olefin-aromatic polyene copolymer in this coordination polymerization step can be controlled by selecting a catalyst or by the monomer concentration in the polymerization liquid under predetermined polymerization conditions. The monomer concentration in the polymerization liquid can generally be controlled by the partial pressure of ethylene gas or the partial pressure of the olefin monomer, or by introducing a measured amount of monomer into the polymerization vessel. The molecular weight and molecular weight distribution of the ethylene-olefin-aromatic polyene copolymer can generally be controlled by selecting a catalyst or the polymerization temperature, or by adding an appropriate chain transfer agent.
[0019] The single-site coordination polymerization catalyst used in the coordination polymerization step is composed of a transition metal compound and a cocatalyst. A known single-site coordination polymerization catalyst can be used in the present invention. The single-site coordination polymerization catalyst, particularly the transition metal compound, may be used alone or in combination. For example, the single-site coordination polymerization catalyst described in WO2000 / 037517 and WO2007 / 139116, and rac-ethylenebis(indenyl)zirconium(IV) dichloride manufactured by Koei Chemical Co., Ltd. can be used.
[0020] The cocatalyst used together with the transition metal compound is not particularly limited, and a known cocatalyst used in combination with a known transition metal compound can be used. As such a cocatalyst, alumoxane such as methylaluminoxane (hereinafter, also referred to as methylalumoxane or MAO) and / or a boron compound are preferred in terms of high activity in polymerization reaction. Examples of the cocatalyst include cocatalysts and alkylaluminum compounds described in JP-A-11-130808, JP-A-9-309925, WO2000 / 020426, JP-A-2000-143733, and JP-A-6-184179. The molar ratio of aluminum atom / transition metal atom of the cocatalyst such as alumoxane is preferably 0.1 to 100,000, more preferably 10 to 10,000, relative to the metal of the transition metal compound. When the molecular weight is 0.1 or more, the transition metal compound can be effectively activated, and when the molecular weight is 100,000 or less, the amount of the promoter used can be reduced, which is economically advantageous.
[0021] On the other hand, when a boron compound is used as the co-catalyst, the ratio of boron atom / transition metal atom is preferably 0.01 to 100 in molar ratio, more preferably 0.1 to 10, and most preferably 1.0. If it is 0.01 or more, the transition metal compound can be effectively activated, and if it is 100 or less, the amount of the co-catalyst added can be reduced, which is economically advantageous. Regardless of the material used as the co-catalyst, the transition metal compound and the co-catalyst may be mixed and prepared outside the polymerization equipment, or may be mixed inside the equipment during polymerization.
[0022] In producing an ethylene-olefin-aromatic polyene copolymer in the coordination polymerization step of producing a graft copolymer, the above-exemplified monomers, transition metal compound, and cocatalyst are contacted, and the order and method of contacting may be any known method.
[0023] Examples of the copolymerization method include a method of polymerization in liquid monomer without using a solvent, or a method of using a single solvent or a mixed solvent of saturated aliphatic, aromatic, and halogenated hydrocarbons such as pentane, hexane, heptane, cyclohexane, benzene, toluene, ethylbenzene, xylene, chloro-substituted benzene, chloro-substituted toluene, methylene chloride, and chloroform. Among these, one or more selected from alkane-based solvents, cyclohexane, toluene, and ethylbenzene are preferred. The polymerization form may be either solution polymerization or slurry polymerization. If necessary, known methods such as batch polymerization, continuous polymerization, prepolymerization, and multistage polymerization can be used.
[0024] It is also possible to use a single tank type polymerization tank, multiple tank type polymerization tanks connected together, or a pipe polymerization system in which a single or multiple linear or loop polymerization tanks are connected together. The pipe type polymerization tank may have various mixers such as a dynamic or static mixer or a static mixer also used for heat removal, or various coolers such as a cooler equipped with a thin tube for heat removal. The pipe type polymerization tank may have a batch type prepolymerization tank. The polymerization temperature is preferably -78 to 200°C, more preferably 0 to 160°C, and most preferably 30 to 160°C. A temperature of -78°C or higher is industrially advantageous, and a temperature of 200°C or lower does not cause decomposition of the transition metal compound. The pressure during polymerization is preferably 0.1 to 100 atm, more preferably 0.1 to 30 atm, and most preferably 0.1 to 1 atm.
[0025] In the grafting step of the production method of the present invention, a graft copolymer containing an ethylene-olefin-aromatic polyene copolymer and an aromatic vinyl compound polymer is synthesized using an aromatic vinyl compound monomer and an anionic polymerization initiator or a radical polymerization initiator. Here, the ethylene-olefin-aromatic polyene copolymer is the copolymer obtained in the coordination polymerization step. The amount of the polymerization initiator (for example, an anionic polymerization initiator or a radical polymerization initiator) used in this grafting step is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of the monomer (for example, styrene monomer).
[0026] The grafting step of the present invention is carried out after the coordination polymerization step. In this case, it is preferable to separate and purify the copolymer obtained in the coordination polymerization step from the polymerization liquid using any polymer recovery method such as a crumb foaming method, a steam stripping method, a direct solvent removal method using a devolatilizer tank, a devolatilizer extruder, etc., and then use it in the grafting step. However, it is economically preferable to use the polymerization liquid after the coordination polymerization in the next step after depressurizing the residual olefin or without depressurizing. One of the features of the present invention is that the polymerization liquid containing the copolymer obtained in the coordination polymerization step can be used in the grafting step without separating the copolymer obtained in the coordination polymerization step from the polymerization liquid.
[0027] When an anionic polymerization initiator is used in the grafting step, that is, when an anionic polymerization is performed, the solvent is preferably a mixed alkane solvent that does not cause problems such as chain transfer during anionic polymerization, such as cyclohexane or benzene, but other solvents such as toluene or ethylbenzene can also be used as long as the polymerization temperature is 150° C. or lower. Any known method used in anionic polymerization can be used as the polymerization form. The grafting step may be either a graft-from method in which an anionic polymerization initiator is added to an ethylene-olefin-aromatic polyene copolymer and an aromatic vinyl compound monomer is added, or a graft-to method in which an ethylene-olefin-aromatic polyene copolymer is added to a mixture of an aromatic vinyl compound monomer and an anionic polymerization initiator.
[0028] In the grafting step of the present invention, a known anionic polymerization initiator can be used. Among these, one or more selected from lithium salts or sodium salts of biphenyl, naphthalene, pyrene, etc., and alkyllithium compounds are preferred, and alkyllithium compounds are most preferred. Among the alkyllithium compounds, one or more selected from sec-butyllithium and n(normal)-butyllithium are preferred. In addition, a multifunctional initiator, a dilithium compound, or a trilithium compound may be used. Furthermore, a known anionic polymerization terminal coupling agent may be used as necessary.
[0029] When a radical polymerization initiator is used in the grafting step, that is, when radical polymerization is carried out, the method described in WO2000 / 037517 is adopted. In carrying out the grafting step of the present invention, anionic polymerization is preferred since the polymerization rate is high, a high monomer conversion rate can be obtained in a short time, and a conversion rate of substantially 100% can be easily obtained.
[0030] The graft copolymer used in the present invention will be described below. This graft copolymer is a copolymer having an ethylene-olefin-aromatic polyene copolymer chain, which is the main chain of the graft copolymer, and an aromatic vinyl compound polymer chain, which is the side chain of the graft copolymer. This graft copolymer is a polymer having a structure in which an ethylene-olefin-aromatic polyene copolymer chain and an aromatic vinyl compound polymer chain are bonded to an aromatic polyene unit. The fact that an ethylene-olefin-aromatic polyene copolymer chain and an aromatic vinyl compound polymer chain are bonded to an aromatic polyene unit can be proven by the following observable phenomenon. Here, a representative example in which an ethylene-1-hexene-divinylbenzene copolymer chain and a polystyrene chain are bonded to a divinylbenzene unit will be shown. That is, the ethylene-1-hexene-divinylbenzene copolymer obtained in the coordination polymerization step and the graft copolymer obtained through anionic polymerization of this copolymer and the presence of styrene monomer will be shown. 1 H-NMR (proton NMR) is measured, and the peak intensities of the vinyl group hydrogen (proton) of the divinylbenzene unit of both are compared using an appropriate internal standard peak (an appropriate peak derived from ethylene-1-hexene-divinylbenzene copolymer). Here, the peak intensity (area) of the vinyl group hydrogen (proton) of the divinylbenzene unit of the graft copolymer is less than 50%, preferably less than 20%, compared with the same peak intensity (area) of the divinylbenzene unit of the ethylene-1-hexene-divinylbenzene copolymer. During anionic polymerization (grafting step), in the case of the graft-to method, polystyrene previously polymerized by anionic polymerization is copolymerized with divinylbenzene. During anionic polymerization (grafting step), in the case of the graft-from method, polystyrene is copolymerized by lithiating the vinyl group of divinylbenzene and adding a styrene monomer. Therefore, in the graft copolymer after anionic polymerization, the peak intensity of the hydrogen (proton) of the vinyl group of the divinylbenzene unit is greatly reduced. In fact, the hydrogen (proton) peak of the vinyl group of the divinylbenzene unit substantially disappears in the graft copolymer after anionic polymerization.
[0031] From another perspective, the fact that in this graft copolymer, the ethylene-olefin-aromatic polyene copolymer chain and the aromatic vinyl compound polymer chain are bonded to the aromatic polyene unit (for example, the ethylene-1-hexene-divinylbenzene copolymer chain and the polystyrene chain are bonded to the divinylbenzene unit) can be proven by the following observable phenomenon. That is, even if this graft copolymer is subjected to solvent fractionation using an appropriate good solvent and a poor solvent, the ethylene-1-hexene-divinylbenzene copolymer chain and the polystyrene chain contained therein cannot be separated as their respective homopolymers. An example is shown below. 400 ml of acetone and a stirrer were placed in a large container and stirred on a magnetic stirrer in an ice bath. 40 ml of toluene and 4 g of the graft copolymer were added to a separate container and heated and stirred to completely dissolve. After dissolving, the heated solution was sucked up with a syringe and slowly dropped into the stirred acetone. After the dropwise addition was completed, the acetone suspension containing the precipitated polymer was filtered under reduced pressure, and the acetone-insoluble polymer remaining on the filter was naturally dried and then vacuum-dried at 60°C overnight to obtain the acetone-insoluble portion. The filtrate was transferred to an eggplant-shaped flask for an evaporator, and the solvent was removed under reduced pressure using a rotary evaporator to extract about 10 ml of concentrated liquid. The eggplant flask was washed several times with a small amount of acetone, and the washings were added to the concentrated liquid. This was poured into about 1 L of vigorously stirred methanol to precipitate the acetone-soluble polymer, which was then filtered under reduced pressure. The polymer on the filter was naturally dried and then vacuum-dried at 60°C overnight. The amount of acetone-soluble polymer is relatively small (several mass % to 20 mass % of the graft copolymer used). 1 It can be confirmed that the polymer is a polystyrene homopolymer by H-NMR measurement. In the examples, the mass average molecular weight of the acetone-soluble polymer is estimated as the mass average molecular weight of the aromatic vinyl compound polymer constituting the side chain. On the other hand, the acetone insolubles accounted for the majority (more than half), and the acetone insoluble polymers 1When measuring H-NMR, both the ethylene-1-hexene-divinylbenzene copolymer chains and the polystyrene chains can be observed, indicating that the ethylene-1-hexene-divinylbenzene copolymer chains and the polystyrene chains contained cannot be separated as their respective homopolymers. To verify that the solvent fractionation was complete, the following procedure was carried out. The above acetone-insoluble polymer was used to carry out solvent fractionation again in the same manner as above, and the acetone-insoluble polymer was recovered. 1 H-NMR measurement was performed. It was confirmed that there was essentially no change in the obtained composition (the composition of ethylene-1-hexene-divinylbenzene copolymer chains and polystyrene chains). In fact, the solvent fractionation was essentially completed with one solvent fractionation.
[0032] From the above, the graft copolymer used in the present invention is a copolymer having an ethylene-olefin-aromatic polyene copolymer chain and an aromatic vinyl compound polymer chain. The graft copolymer used in the present invention is a copolymer having a structure in which an ethylene-olefin-aromatic polyene copolymer chain and an aromatic vinyl compound polymer chain are bonded to an aromatic polyene unit. More preferably, the graft copolymer is a copolymer characterized by any one of the following (1) to (3) or a combination thereof. (1) The composition of the ethylene-olefin-aromatic polyene copolymer obtained in the coordination polymerization step is an olefin content of 3 to 50 mol% (for example, within a range between any two numerical values selected from the group consisting of 3, 5, 10, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 35, 40, and 50 mol%), an aromatic polyene content of 0.1 to 1 mol% (for example, within a range between any two numerical values selected from the group consisting of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and 1.0 mol%), and the remainder being an ethylene content. (2) The mass average molecular weight (Mw) of the ethylene-olefin-aromatic polyene copolymer obtained in the coordination polymerization step is 50,000 to 100,000 (for example, within a range between two arbitrary numerical values selected from the group consisting of 50,000, 60,000, 65,000, 66,000, 67,000, 68,000, 69,000, 70,000, 71,000, 72,000, 73,000, 74,000, 75,000, 76,000, 77,000, 78,000, 79,000, 80,000, 90,000 and 100,000). The molecular weight distribution (Mw / Mn) of the ethylene-olefin-aromatic polyene copolymer is preferably 6 or less, more preferably 4 or less, and most preferably 3 or less. The molecular weight distribution of the ethylene-olefin-aromatic polyene copolymer is preferably 1.8 or more, more preferably 2.0 or more. (3) The mass average molecular weight (Mw) of the aromatic vinyl compound polymer constituting the side chain is 5,000 to 50,000 (for example, within a range between two arbitrary numerical values selected from the group consisting of 5,000, 10,000, 20,000, 25,000, 26,000, 27,000, 28,000, 29,000, 30,000, 31,000, 32,000, 33,000, 34,000, 35,000, 37,000, 38,000, 39,000, 40,000 and 50,000). The molecular weight distribution (Mw / Mn) of the aromatic vinyl compound polymer constituting the side chain is preferably 6 or less, more preferably 4 or less, and most preferably 3 or less. The molecular weight distribution of the aromatic vinyl compound polymer constituting the side chain is preferably 1.0 or more. The mass average molecular weight and molecular weight distribution of the aromatic vinyl compound polymer constituting the side chain are estimated from the molecular weight of the homopolymer not grafted. The mass average molecular weight of the aromatic vinyl compound polymer constituting the side chain may be the mass average molecular weight and molecular weight distribution of the homopolymer not grafted. In addition, the content of the aromatic vinyl compound polymer constituting the side chain in the graft copolymer is 5 to 60 wt% (hereinafter, wt% may also be referred to as mass%) (for example, within a range between any two numerical values selected from the group consisting of 5, 7, 9, 10, 15, 20, 25, 30, 40, 45, 50, 55 and 60 wt%).
[0033] <Composition> The graft copolymer has good compatibility with polypropylene-based resins and olefin-based resins, and in a resin phase separation structure observed with a transmission electron microscope, the dispersed phase c of the graft copolymer, i.e., the dispersed phase c consisting of an aromatic vinyl-based resin, has an average equivalent circle diameter of 50 nm to 1 μm (for example, within a range between any two numerical values selected from the group consisting of 50, 60, 70, 80, 90, 100, 110, 120, 150, 200, 300, 310, 320, 400, 600, 800, and 1000 nm), and an average center-of-gravity distance of 300 nm or more and 1500 nm or less (for example, within a range between any two numerical values selected from the group consisting of 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, and 1500 nm), and the composition has excellent tensile properties and impact resistance. The average equivalent circle diameter refers to the average value of the diameter of the circle equivalent to the area of the observed dispersed phase C. The average distance between the centers of gravity refers to the average value of the shortest distance between the centers of gravity of adjacent dispersed phases C. When the average equivalent circle diameter of the dispersed phase of the graft copolymer is smaller than 50 nm or larger than 1 μm, the brittle-ductile transition is not induced in the matrix around the dispersed phase of the graft copolymer, and practical impact strength is not obtained. Also, when the average center-to-center distance of the dispersed phase of the graft copolymer is smaller than 300 nm or larger than 1500 nm, dispersion is poor and stable impact strength is not obtained.
[0034] The dispersed phase of the graft copolymer can be stained with RuO4 vapor. In the electron microscope photograph, the darkly stained portion is the styrene domain of the graft copolymer (dispersed phase of the graft copolymer). Figure 1 shows a schematic diagram of a resin phase separation structure observed with a transmission electron microscope. a shows a continuous phase made of polypropylene, b shows a dispersed phase (gray) containing an olefin-based resin, and c shows a dispersed phase (black; also referred to as the dyed portion) made of an aromatic vinyl-based resin. Dispersed phase c includes dispersed phase c1 present in continuous phase a, dispersed phase c2 present in dispersed phase b, and dispersed phase c3 present at the interface between continuous phase a and dispersed phase b. The circle equivalent diameter and center-of-gravity distance of this darkly stained portion can be measured using image analysis software WinROOF2018 (manufactured by Mitani Shoji Co., Ltd.). The average circle equivalent diameter and center-of-gravity distance can be calculated from multiple (e.g., four) photographs with different fields of view.
[0035] <Polypropylene resin and olefin resin> The polypropylene resin is a polymer mainly composed of propylene. It is preferably a homopolypropylene (propylene homocopolymer, hereinafter sometimes referred to as homoPP), a block polypropylene (hereinafter sometimes referred to as block PP), a random polypropylene, or a mixture thereof. Examples of the block PP and the random polypropylene include an α-olefin-propylene copolymer, which will be described later. From the viewpoint of the rigidity and impact resistance of the composition, one or more members of the group consisting of homopolypropylene and block PP are preferred. As for the homopolypropylene and block polypropylene, those described in, for example, JP-A-11-29690 and JP-A-11-29669 can also be suitably used. The olefin resin is preferably a polymer mainly composed of an olefin monomer having 2 to 20 carbon atoms. The olefin resin does not include a polypropylene resin or an aromatic vinyl resin. Preferred examples include cyclic olefin polymers such as polyethylene, polyisobutene, polybutene, and polynorbornene, and cyclic olefin copolymers such as ethylene-norbornene copolymer. If necessary, an olefin resin copolymerized with dienes such as butadiene and α-ω diene may be used. Among these, polyethylene is preferred. In this embodiment, it is preferable to use an α-olefin-propylene copolymer as the resin containing the polypropylene-based resin and the olefin-based resin. The α-olefin is one other than propylene. Examples of the α-olefin include ethylene, 1-butene, 2-methyl-1-propene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 2-ethyl-1-butene, 2,3-dimethyl-1-butene, 2-methyl-1-pentene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, ethyl-1-pentene, trimethyl-1-butene, and 1-octene. One or more of these may be copolymerized with propylene. Among the α-olefins, ethylene is preferable in terms of impact resistance. The α-olefin-propylene copolymer is preferably a block copolymer. The α-olefin-propylene copolymer contains propylene units in an amount of preferably 75 to 99.5% by mass, more preferably 80 to 90% by mass. The α-olefin-propylene copolymer contains α-olefin units in an amount of preferably 0.5 to 25% by mass, more preferably 10 to 20% by mass. When the α-olefin units are 0.5% by mass or more, the impact resistance is improved. When the α-olefin units are 25% by mass or less, the rigidity and the like are improved. In the examples, the following commercially available polypropylene resins and olefin resins were used: Novatec PP BC03B (manufactured by Japan Polypropylene Corporation, MFR: 30 g / 10 min, ethylene-propylene block copolymer). The melt flow rate (MFR) of the polypropylene resin and the olefin resin is preferably 5 to 70 g / 10 min, more preferably 10 to 40 g / 10 min. If the MFR is 5 g / 10 min or more, the processability is improved. If the MFR is 70 g / 10 min or less, the impact strength is improved. The MFR is preferably measured in accordance with Method A of JIS K7210:1999 at a temperature of 230° C. and a load of 2.16 kg. This embodiment preferably contains 50 to 90 wt% of polypropylene resin (A), 5 to 25 wt% of olefin resin (B), and 5 to 25 wt% of aromatic vinyl resin (C). The total of the polypropylene resin (A), the olefin resin (B), and the aromatic vinyl resin (C) is preferably 100 wt%.
[0036] The above definitions will be explained below from the viewpoint of the tensile properties, impact resistance, and dispersibility of the finally obtained composition of the present invention. The composition of the present invention has tensile properties, impact resistance, and dispersibility, and is therefore extremely useful as a thermoplastic elastomer. Specifically, the composition of the present invention has a tensile modulus of 700 to 1100 MPa (for example, within a range between any two numerical values selected from the group consisting of 700, 750, 800, 840, 850, 870, 900, 920, 950, 1000, 1050, and 1100 MPa), a breaking elongation of 90 to 300% (for example, within a range between any two numerical values selected from the group consisting of 90, 100, 120, 150, 200, 220, 250, and 300%), a breaking strength of 10 to 18 MPa (for example, within a range between any two numerical values selected from the group consisting of 10, 11, 12, 13, 14, 15, 16, 17, and 18 MPa), and a Charpy impact strength at 23° C. of 5 to 25 kJ / m 2 (e.g., 5, 7, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 24 and 25 kJ / m 2 and any two numbers selected from the group consisting of:
[0037] The composition of the present invention may contain other resins, elastomers, and rubbers, if necessary, within the scope of not impairing the object of the present invention.Furthermore, known fillers, stabilizers, antioxidants, light resistance improvers, ultraviolet absorbers, softeners, lubricants, processing aids, colorants, antistatic agents, antifogging agents, antiblocking agents, crystal nucleating agents, foaming agents, etc., which are generally added to resin compositions, may be used.
[0038] To produce the composition of the present invention, a known appropriate kneading method can be used. For example, melt mixing can be performed using a single-screw or twin-screw extruder, a Banbury mixer, a plastomill, a co-kneader, a heating roll, or the like. Before melt mixing, each raw material may be mixed uniformly using a Henschel mixer, a ribbon blender, a super mixer, a tumbler, or the like. There are no particular limitations on the melt kneading temperature, but it is preferably 100 to 300°C, more preferably 150 to 250°C.
[0039] The composition of the present invention can be molded by known molding methods such as vacuum molding, injection molding, blow molding, and extrusion molding.
[0040] The composition of the present invention may be a resin composition.
[0041] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted.
[0042] The present invention will be further described below with reference to examples, but the present invention is not limited to these. EXAMPLES
[0043] [Analysis and evaluation method] The copolymers obtained in the examples were analyzed by the following methods.
[0044] ( 1 H-NMR spectrum) The content of each unit of olefin and aromatic vinyl compound in the copolymer is determined as follows: 1The measurement was performed by H-NMR, using instruments α-500 manufactured by JEOL and AC-250 manufactured by BRUCKER. The polymer was dissolved in heavy 1,1,2,2-tetrachloroethane, and if it was soluble at room temperature, it was measured at room temperature, and if it was not soluble at room temperature, it was measured at 80 to 100°C. The content and composition of each unit were determined by comparing the areas of the peaks derived from each unit obtained by a known method. The mass% of the aromatic vinyl polymer obtained in the grafting step was also determined in the same manner.
[0045] (Gas Chromatography Analysis) The content of aromatic polyene units (divinylbenzene units) in the resin was calculated from the difference between the amount of unreacted divinylbenzene in the polymerization liquid determined by gas chromatography analysis and the amount of divinylbenzene used in the polymerization.
[0046] (molecular weight measurement) The molecular weight was determined by high-temperature GPC (gel permeation chromatography) using the weight average molecular weight (Mw) and number average molecular weight (Mn) converted into standard polystyrene. The measurement was performed under the following conditions. Equipment: Tosoh HLC-8121GPC / HT Column: TSKgelGMHHR-H(20)HT, φ7.8×300mm x 3, Column temperature: 140℃, Detector: RI (Differential refractive index detector), Solvent: orthodichlorobenzene, Flow rate: 1.0ml / min, Sample concentration: 0.1wt / vol%, Sample injection volume: 100μL
[0047] (Sample sheet creation) The samples for evaluating physical properties were prepared by the hot press method (temperature 200°C, time 5 minutes, pressure 50 kg / cm 2 A 0.5 mm thick sheet molded using the above process was used.
[0048] (Tensile test: tensile modulus, elongation at break (elongation at break), strength at break (strength at break)) In accordance with JIS K6251, a 0.5 mm thick sheet was cut into a No. 2 1 / 2 test piece shape and measured using a Shimadzu AGS-100D tensile testing machine at 23±1°C and a tensile speed of 50 mm / min.
[0049] (Preparation of injection molded pieces) Test pieces for physical property analysis were molded by injection molding. They were processed into JIS K7139 multipurpose test pieces type A1 (h (thickness) was 4 mm) under molding conditions conforming to JIS K7152-1.
[0050] (23℃ Charpy impact strength) The measurement was performed with a notch in accordance with JIS K7111-1.
[0051] (Transmission Electron Microscope) After staining overnight with RuO4 vapor, the sample was cut out with a diamond knife and observed. Figure 1 shows a schematic diagram of the resin phase separation structure observed with a transmission electron microscope. a shows a continuous phase made of polypropylene, b shows a dispersed phase (gray) containing an olefin (especially ethylene) resin, and c shows a dispersed phase (black; also called the dyed part) made of an aromatic vinyl resin. Dispersed phase c includes dispersed phase c1 present in continuous phase a, dispersed phase c2 present in dispersed phase b, and dispersed phase c3 present at the interface between continuous phase a and dispersed phase b. In the electron microscope photograph obtained under these conditions, dispersed phase c is a styrene domain of the graft copolymer. The circle equivalent diameter and center-of-gravity distance of this dispersed phase c were measured using the image analysis software WinROOF2018, and the average values were calculated from four photographs with different fields of view.
[0052] [Example A] (Preparation of Graft Copolymer) The reaction was carried out as follows using rac-ethylenebis(indenyl)zirconium(IV) dichloride, manufactured by Koei Chemical Co., Ltd., and represented by the following general formula (A), as a catalyst.
[0053] [ka]
[0054] Under the polymerization conditions shown in Table 1, a 10L polymerization tank equipped with a stirrer and a jacket for heating and cooling was used, and 3.7 kg of cyclohexane solvent, 1.05 kg of 1-hexene monomer ("Olefin" in Table 1, Linearene 6 manufactured by Idemitsu Kosan Co., Ltd.) and 0.1 kg of divinylbenzene ("DVB" in Table 1, Divinylbenzene 810 manufactured by Nippon Steel Chemical Materials Co., Ltd.) were charged and heated and stirred at an internal temperature of 40°C. About 100 L of dry nitrogen gas was bubbled in to purge the moisture in the system and the polymerization liquid. Next, the internal temperature was raised to 60°C, 3 mmol of triisobutylaluminum ("TIBA" in Table 1) was added, and further 6 mmol of MAO (modified MAO: MMAO manufactured by Tosoh Finechem Co., Ltd.) was added, and ethylene was immediately introduced. After the pressure of the polymerization vessel after ethylene was introduced ("Ethylene" in Table 1) stabilized at 0.20 MPa, a catalyst solution consisting of 20 ml of a toluene solution containing 6 mmol of MMAO and 12 μmol of rac-ethylenebis(indenyl)zirconium(IV) dichloride ("Catalyst" in Table 1) was added to the autoclave from a catalyst tank installed on the autoclave to start the coordination polymerization process. The polymerization was carried out while maintaining the internal temperature ("Temperature" in Table 1) at 85°C and the pressure at 0.20 MPa. When the cumulative ethylene flow rate ("Ethylene consumption" in Table 1) reached 260 L, the ethylene supply was stopped, the pressure was released, and sampling was performed. From this sampled solution, the composition and molecular weight of the polymer obtained in the coordination polymerization process were determined. Next, 100 mmol of n-BuLi (n-butyl lithium, "BuLi" in Table 1) and THF (200 ppm relative to the total amount of the polymerization solution) were added at room temperature and reacted for 1 hour. 2.0 kg of styrene monomer ("styrene" in Table 1) was added and a grafting reaction (anionic polymerization step) was carried out to synthesize a graft copolymer. The resulting polymerization solution was gradually poured into a large amount of acetone that was being vigorously stirred, filtered, and the acetone-insoluble polymer was recovered as a graft copolymer. This graft copolymer was dried in a vacuum dryer until no change in mass was observed. An acetone-soluble polymer was precipitated from the filtrate and recovered.
[0055] [Examples B, C, and D] Polymerization was carried out under the polymerization conditions shown in Table 1 in the same manner as in Example A.
[0056] [Table 1]
[0057] [Comparative Example A] (Preparation of Cross-Copolymer) Diphenylmethylene(fluorenyl)(cyclopentadienyl)zirconium dichloride (see general formula (B) below) was used as the catalyst ("Catalyst" in Table 1). Diphenylmethylene(fluorenyl)(cyclopentadienyl)zirconium dichloride was synthesized using diphenylfulvene, cyclopentadiene (dicyclopentadiene) and fluorene as ligand raw materials, with reference to the manufacturing method described in J. Am. Chem. Soc., 110, 6255 (1988).
[0058] [ka]
[0059] Under the polymerization conditions shown in Table 1, after the coordination polymerization step was carried out in the same manner as in the examples, 0.1 kg of styrene monomer was added, and after thorough stirring and mixing, 145 mmol of n-BuLi was added, and a cross-polymer was synthesized by carrying out a cross-polymerization step (anionic polymerization step) while maintaining the temperature at 65 to 70°C. The obtained polymerization liquid was gradually poured into a large amount of vigorously stirred methanol, filtered, and a methanol-insoluble polymer was recovered as a cross-copolymer. This cross-copolymer was air-dried at room temperature for one day and night, and then dried in a vacuum at 80°C until no mass change was observed. A methanol-soluble polymer was precipitated from the filtrate and recovered.
[0060] [Comparative example B] Polymerization was carried out under the polymerization conditions shown in Table 1 in the same manner as in Comparative Example A.
[0061] Table 2 shows the analytical results of the ethylene-olefin-aromatic polyene copolymer obtained in the coordination polymerization step in each Example and Comparative Example, and the graft copolymer and cross copolymer obtained through the grafting step and crossing step. In the item of the coordination polymerization step in Table 2, the values of the ethylene-olefin-aromatic polyene copolymer obtained in the coordination polymerization step are as follows: The olefin content ("α-olefin content" in Table 2) is the olefin content in the ethylene-olefin-aromatic polyene copolymer. The aromatic polyene content ("DVB content" in Table 2) is the aromatic polyene content in the ethylene-olefin-aromatic polyene copolymer. The average molecular weight ("Mw" in Table 2) is the mass average molecular weight of the ethylene-olefin-aromatic polyene copolymer. The molecular weight distribution ("Mw / Mn" in Table 2) is the molecular weight distribution of the ethylene-olefin-aromatic polyene copolymer. The values of polystyrene (PS) in the grafting step (Examples A, B, C, and D) in Table 2 are as follows. The aromatic vinyl compound polymer content constituting the side chain in the graft copolymer ("PS wt%" in Table 2) is the content in the graft copolymer. The average molecular weight ("PS Mw" in Table 2) is the mass average molecular weight of the polystyrene constituting the side chain in the graft copolymer. The molecular weight distribution ("PS Mw / Mn" in Table 2) is the molecular weight distribution of the polystyrene constituting the side chain in the graft copolymer. Here, the average molecular weight and molecular weight distribution of the acetone-soluble polymer are described as the average molecular weight and molecular weight distribution of the polystyrene constituting the side chain in the graft copolymer. The values of polystyrene (PS) in the cross-polymerization process (Comparative Examples A and B) in Table 2 are as follows. The aromatic vinyl compound polymer content constituting the side chain in the cross-copolymer ("PS wt%" in Table 2) is the content in the cross-copolymer. The average molecular weight ("PS Mw" in Table 2) is the mass average molecular weight of the polystyrene constituting the side chain in the cross-copolymer. The molecular weight distribution ("PS Mw / Mn" in Table 2) is the molecular weight distribution of the polystyrene constituting the side chain in the cross-copolymer. Here, the average molecular weight and molecular weight distribution of the methanol-soluble polymer are described as the average molecular weight and molecular weight distribution of the polystyrene constituting the side chain in the cross-copolymer.
[0062] [Table 2]
[0063] (Examples 1 to 4, Comparative Examples 1 to 2) A composition containing polypropylene, an olefin resin, and a styrene resin was obtained as follows: Using a twin-screw extruder (Ikegai Corporation, PCM30), the graft copolymers or cross copolymers obtained in Examples A to D and Comparative Examples A and B, and block polypropylene (Japan Polypropylene Corporation, Novatec PP BC03B: a compound of 84 mass% polypropylene and 16 mass% ethylene, an ethylene-propylene block copolymer) were dry blended and melt kneaded at 200°C according to the composition shown in Table 3.
[0064] As Comparative Example 3, a commercially available SEPS (Septon 2004, manufactured by Kuraray Co., Ltd.) was used instead of the graft copolymer of the present invention, and as Comparative Example 4, a block polypropylene alone was used to obtain a composition in the same manner as in Examples 1 to 4 and Comparative Examples 1 and 2. SEPS is not a polypropylene-based resin (A), is not an olefin-based resin (B), is not an aromatic vinyl-based resin (C), and is not a graft copolymer.
[0065] The physical properties of the compositions obtained in the Examples and Comparative Examples are shown in Table 3. Figure 2 shows a transmission electron microscope photograph of the composition of Example 2 (Figure 2A) and a transmission electron microscope photograph of the composition of Example 3 (Figure 2B).
[0066] [Table 3]
[0067] As shown in Figures 2A and 2B, in the compositions obtained in the Examples, dispersed phase c (c1) was present in continuous phase a, dispersed phase c (c2) was present in dispersed phase b, or dispersed phase c (c3) was present at the interface between continuous phase a and dispersed phase b.
[0068] The composition of the present invention had good tensile properties such as tensile modulus and impact resistance. When the cross copolymer of Comparative Example 1 was used, the physical properties were not evaluated due to poor dispersion. The cross copolymer of Comparative Example 2 had poor elongation at break. Observation with a transmission electron microscope showed that the average equivalent circle diameter and the average center-to-center distance were larger than those of the graft copolymer, which is considered to be due to the fact that the cross copolymer is a high molecular weight substance and therefore has poor dispersibility. In Comparative Examples 3 and 4, the average equivalent circle diameter and the average center-to-center distance could not be measured because no circle was formed.
[0069] The most preferred conditions of the present invention, i.e., the composition of the ethylene-olefin-aromatic polyene copolymer obtained in the coordination polymerization step is an olefin content of 20 to 35 mol%, an aromatic polyene content of 0.1 to 1 mol%, and the remainder is an ethylene content, the mass average molecular weight (Mw) of the ethylene-olefin-aromatic polyene copolymer which is the main chain of the graft copolymer is 50,000 to 100,000, and the styrene content of the side chain of the graft copolymer is 20 to 45 wt%. The mechanical properties of the compositions (Examples 2 and 4) using the graft copolymers of Examples B and D are a tensile modulus of elasticity of 700 to 1100 MPa, a breaking elongation of 90 to 300%, a breaking strength of 10 to 18 MPa, and a Charpy impact strength at 23°C of 5 to 25 kJ / m. 2 The range was met.
[0070] The composition of the present invention has good compatibility with the graft copolymer, olefin-based resin, and polypropylene-based resin, and therefore the graft copolymer is finely dispersed in the polypropylene-based resin and the olefin-based resin, improving mechanical properties such as tensile modulus and impact resistance.
Claims
1. Contains 50-90wt% polypropylene resin (A), 5-25wt% olefin resin (B), and 5-25wt% aromatic vinyl resin (C). A continuous phase a made of the polypropylene-based resin; A dispersed phase b containing the olefin-based resin dispersed in a continuous phase a; The dispersed phase c is made of the aromatic vinyl resin, Dispersed phase c is present in continuous phase a, or dispersed phase c is present in dispersed phase b, or dispersed phase c is present at the interface between continuous phase a and dispersed phase b, In a phase separation structure observed by a transmission electron microscope, the average equivalent circle diameter of the dispersed phase c is 50 nm or more and 1 μm or less, and the average distance between the centers of gravity of the dispersed phase c is 300 nm or more and 1500 nm or less, The aromatic vinyl resin includes a graft copolymer, the main chain of the graft copolymer comprises an ethylene-olefin-aromatic polyene copolymer; The olefin monomer has 3 to 12 carbon atoms, The main chain of the graft copolymer has a composition of 3 to 50 mol % of an olefin content, 0.1 to 1 mol % of an aromatic polyene content, and the remainder being an ethylene content; The main chain of the graft copolymer has a mass average molecular weight of 50,000 to 100,000; a side chain of the graft copolymer contains an aromatic vinyl compound; The composition, wherein the side chain of the graft copolymer has a mass average molecular weight of 0.5 to 50,000.
2. 2. The composition according to claim 1, wherein the polypropylene-based resin (A) and the olefin-based resin (B) comprise an α-olefin-propylene copolymer.
3. The tensile modulus, measured in accordance with JIS K6251 at a tensile speed of 50 mm / min, is 700 to 1100 MPa, the elongation at break is 90 to 300%, and the breaking strength is 10 to 18 MPa. Charpy impact strength measured with a notch at 23°C in accordance with JIS K7111-1 is 5 to 25 kJ / m 2 The composition according to claim 1 or 2,
4. a coordination polymerization step of synthesizing an ethylene-olefin-aromatic polyene copolymer from an ethylene monomer, an olefin monomer, and an aromatic polyene using a single-site coordination polymerization catalyst; a grafting step of synthesizing a graft copolymer containing the ethylene-olefin-aromatic polyene copolymer and an aromatic vinyl compound polymer by using an aromatic vinyl compound monomer and an anionic polymerization initiator or a radical polymerization initiator; and a kneading step of kneading an aromatic vinyl resin (C) containing the graft copolymer produced by a method for producing a graft copolymer, the graft copolymer being produced by a method for producing a graft copolymer comprising the steps of: kneading a polypropylene resin (A) and an olefin resin (B), Contains 50-90wt% polypropylene resin (A), 5-25wt% olefin resin (B), and 5-25wt% aromatic vinyl resin (C). A continuous phase a made of the polypropylene-based resin; A dispersed phase b containing the olefin-based resin dispersed in a continuous phase a; The dispersed phase c is made of the aromatic vinyl resin, Dispersed phase c is present in continuous phase a, or dispersed phase c is present in dispersed phase b, or dispersed phase c is present at the interface between continuous phase a and dispersed phase b, In a resin phase separation structure observed by a transmission electron microscope, the average equivalent circle diameter of the dispersed phase c is 50 nm or more and 1 μm or less, and the average distance between the centers of gravity of the dispersed phase c is 300 nm or more and 1500 nm or less, The graft copolymer is synthesized in solution in a coordination polymerization process, the main chain of the graft copolymer comprises an ethylene-olefin-aromatic polyene copolymer; The olefin monomer has 3 to 12 carbon atoms, The main chain of the graft copolymer has a composition of 3 to 50 mol % of an olefin content, 0.1 to 1 mol % of an aromatic polyene content, and the remainder being an ethylene content; The main chain of the graft copolymer has a mass average molecular weight of 50,000 to 100,000; a side chain of the graft copolymer contains an aromatic vinyl compound; The mass average molecular weight of the side chain of the graft copolymer is 5,000 to 50,000. Method for producing the composition.
5. The method for producing a composition according to claim 4, wherein the polypropylene-based resin (A) and the olefin-based resin (B) contain an α-olefin-propylene copolymer.
Citation Information
Patent Citations
Thermoplastic resin composition
JP1992136052A
Thermoplastic resin composition and molded resin article
JP1993078549A
Polypropylene resin composite composition
JP1996020690A
Thermoplastic resin composition, and filler-including resin composition and molded body using the same
JP2018027994A
Resin composition and resin mold product
JP2020100706A
